(842) On Determining Reorder Point and Reorder Quantity In A Probabilistic Inventory Model تحديد نقطة إعادة الطلب وكمية إعادة الطلب في نموذج المخزون الاحتمالي - El-Shafei, W. A. M.; Mahdy, M. A. M. (The Institute of National Planning, 2024)
In seeking to optimize inventory systems, we may occasionally encounter complex factors that cannot be solved with simple formulas or tabular data. Even advanced mathematical approaches may prove inadequate or too unwieldy. In such situations, the only practical option available is to use simulation techniques, usually with the aid of a computer.